Norm violations and punishment beyond the nation-state: normative orders, authority, and conflict in international society - Wagner, Wolfgang (Punishment in international society, 2024)
Punitive practices are highly revealing of a society’s social fabric, normative order, and power structure. However, the social sciences and humanities have hitherto studied punishment mostly in the context of the nation-state by examining how people, organizations, and legal institutions punish individual offenders within national boundaries. In contrast, this chapter examines punitive practices of international society, where punitive practices have assumed three main forms: sanctions, international courts and tribunals, and the punitive use of armed force. A punitive lens on international affairs contributes to the understanding of international society in three ways: It identifies which norms and values are at the core of the international order and its conception of justice, it helps identify structures of power and authority in international society, and an analysis of the penal philosophies that buttress the punitive enforcement of norms points to the potential for conflict and cooperation in international society.